The role of networks in determining usage of community currencies in Kenya. Issue 2 (3rd April 2019) - Kiguru, Janet Muthoni; Upadhyaya, Radha
ABSTRACT: Past studies have attributed the usage of community currencies to government support, community solidarity, business networks and social networks. Using a mixed-methods approach, this paper examines the role of networks in determining the usage of community currencies in an ethnically heterogeneous community. It argues that while networks are important in determining the usage of community currencies, it is not the presence of networks per se that is important, but the types of networks, the level of trust within them and the kind of information passed on within them, as well as the number of networks to which an individual belongs. The paper makes a contribution by offering a more nuanced view of the role of networks in the adoption of community currencies among the poor.